2023
DOI: 10.1101/2023.07.20.549758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning illuminates how diet influences the evolution of yeast galactose metabolism

Abstract: How genomic differences contribute to phenotypic differences across species is a major question in biology. The recently characterized genomes, isolation environments, and qualitative patterns of growth on 122 sources and conditions of 1,154 strains from 1,049 fungal species (nearly all known) in the subphylum Saccharomycotina provide a powerful, yet complex, dataset for addressing this question. In recent years, machine learning has been successfully used in diverse analyses of biological big data. Using a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This comprehensive dataset and analytical framework provide the opportunity to study how the observed genomic, metabolic, and environmental variation across the subphylum is associated with any complex trait of interest (68)(69)(70). To illustrate this potential, we examined the metabolic niche breadths of yeast pathogens of humans compared with those of their nonpathogenic close relatives (using a specific phylogenetic distance cutoff to standardize the clades) (Fig.…”
Section: Human Yeast Pathogens Include Both Carbon Generalists and Sp...mentioning
confidence: 99%
“…This comprehensive dataset and analytical framework provide the opportunity to study how the observed genomic, metabolic, and environmental variation across the subphylum is associated with any complex trait of interest (68)(69)(70). To illustrate this potential, we examined the metabolic niche breadths of yeast pathogens of humans compared with those of their nonpathogenic close relatives (using a specific phylogenetic distance cutoff to standardize the clades) (Fig.…”
Section: Human Yeast Pathogens Include Both Carbon Generalists and Sp...mentioning
confidence: 99%
“…Supervised models rely on labeled training data as input [e.g., random forest (RF), logistic regression (LR)], whereas unsupervised ones use unlabeled raw data (e.g., neural network, hidden Markov model) to enable predictions/classifications given sufficient data. Machine learning models have been successfully used to predict both genomic features ( 31 ) and phenotypic traits ( 32 34 ) and can be used with any type of biological, including genomic, data ( 35 ).…”
Section: Introductionmentioning
confidence: 99%